2022
DOI: 10.1111/ajco.13732
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cabazitaxel: Late line treatments in metastatic castration resistant prostate cancer: A retrospective multicentre analysis

Abstract: Aims Multiple life‐prolonging therapies are available for metastatic castration‐resistant prostate cancer (mCRPC). However, the optimal treatment strategy following progression through standard treatment with docetaxel, androgen receptor signaling inhibitor (ARSI) and cabazitaxel, remains unclear. We aimed to describe treatment patterns in men with mCRPC following progression on standard treatments and determine whether subsequent treatment choice impacts overall survival. Methods Clinicopathologic and treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…An Australian study found longer OS in patients who received subsequent treatment beyond cabazitaxel in patients who received ARSI, docetaxel, and cabazitaxel, than in those without further therapy after cabazitaxel. 2 Conversely, that study found no OS difference when comparing different treatment groups, probably by the different agents they used after cabazitaxel such as cyclophosphamide, or trials, that were not used in this study. Therefore, further research is required to know the role of each agent after cabazitaxel to prolong OS.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…An Australian study found longer OS in patients who received subsequent treatment beyond cabazitaxel in patients who received ARSI, docetaxel, and cabazitaxel, than in those without further therapy after cabazitaxel. 2 Conversely, that study found no OS difference when comparing different treatment groups, probably by the different agents they used after cabazitaxel such as cyclophosphamide, or trials, that were not used in this study. Therefore, further research is required to know the role of each agent after cabazitaxel to prolong OS.…”
mentioning
confidence: 57%
“…1 Little is known about survival in subsequent treatment beyond cabazitaxel. 2 Therefore, we described the treatment patterns in mCRPC beyond cabazitaxel and determined its impact on survival.…”
mentioning
confidence: 99%
“…The most frequent 1L-to-2L treatment sequence in a large retrospective study in the US was abiraterone-to-enzalutamide, followed by enzalutamide-to-abiraterone ( 82 ), while in Ontario, Canada, the preference was to provide a subsequent (2L) treatment with a different mechanism of action (abiraterone or enzalutamide followed by docetaxel, with Ra-223 being the most common 3L treatment) ( 80 ). A retrospective, multicenter analysis of real-world data performed in Australia found that the most frequent subsequent systemic therapy was a carboplatin-based regimen, and that some patients also received rechallenge with an ARPI or docetaxel ( 106 ). However, it was also reported that choice of subsequent treatment did not impact survival outcomes; median OS did not differ according to subsequent systematic therapy ( 106 ).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective, multicenter analysis of real-world data performed in Australia found that the most frequent subsequent systemic therapy was a carboplatin-based regimen, and that some patients also received rechallenge with an ARPI or docetaxel ( 106 ). However, it was also reported that choice of subsequent treatment did not impact survival outcomes; median OS did not differ according to subsequent systematic therapy ( 106 ). In contrast, in a single-center study, docetaxel rechallenge has shown meaningful anti-tumor activity in pretreated patients with mCRPC in the salvage setting ( 107 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation